Coal Consumption and Economic Growth: Evidence from a panel of OECD countries - Apergis, Nicholas; Payne, J. (Elsevier Science Ltd., 2010)
This study examines the relationship between coal consumption and economic growth for 25 OECD countries within a multivariate panel framework over period 1980–2005. The Larsson et al. (2001) panel cointegration test indicates there is a long-run equilibrium relationship between real GDP, coal consumption, real gross fixed capital formation, and the labor force. The respective coefficients for real gross fixed capital formation and the labor force are positive and statistically significant whereas the coefficient for coal consumption is negative and statistically significant. The results of the panel vector error correction model reveal bidirectional causality between coal consumption and economic growth in both the short- and long-run; however, the bidirectional causality in the short-run is negative.